BE A GLOBAL PLAYER 08 IN SUSTAINABILITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 December 2016 – The International Conference on Sustainable Development Goals (ICSDG2016) serves as a platform on the sharing and exchange of ideas, opinions, recommendations and solutions, to benefit all of us and to ensure that we could strive for a bettermanaged and more prosperous world.